Rente as Proof of Land Ownership - Alimuddin, Nur Hidayani (Jurnal Mulawarman Law Review, 2019)
Rente or proof of payment of land taxes is no longer able used as proof of landownership, however there still people who think rente as proof of land ownership. This research is juridical empirical that analyze the position and perception of society that think rente as proof of ownership of the land in Pangkajene Islands Regency. The result of the study are rente position after the enactment of the Basic Agrarian Law is no longer able to be used as proof of land ownership. On the other hand the National Land Board still receive rente as written evidence to register a land, and there are still people who think rente as proof of land ownership.